Engineered Aluminium Beams for Anchoring Timber Buildings to Foundation. Issue 2 (1st May 2017) - Scotta, Roberto; Marchi, Luca; Trutalli, Davide; Pozza, Luca
Abstract: This paper reports the structural characterization of an innovative engineered aluminium beam, used as bottom rail for timber shear walls, capable of overcoming the crucial durability problem that could affect the timber shear walls near the foundations, at the same time improving the precision and speed of installation. Traditional techniques have disadvantages such as excessive geometric inaccuracies, difficulty in achieving efficient and long-lasting solutions, compression orthogonal to the wood grain, reduced durability due to increasing dampness and problems with waterproofing. Results from laboratory tests conducted to verify the mechanical behaviour of this innovative bottom rail when subjected to tension and compression perpendicular to its axis are reported in comparison with numerical provisions. The ultimate strength of the aluminium-to-timber connections, specifically developed to be compatible with the beam and easily installable, was also obtained. The results demonstrate that this innovative technology ensures the achievement of the expected static performances. Installation and durability advantages are highlighted and the first utilization of the aluminium beam is illustrated.